Synthesis of Uracil-, Coumarin- and Quinolone-Fused Benzosultams and Benzosultones - Mondal, Shovan; Debnath, Sudarshan; Pal, Subhajit; Das, Arko (Synthesis, 2015)
An efficient method for the regioselective synthesis of uracil-, coumarin- and quinolone-fused benzosultams and benzosultones is reported. The method offers a synthetic route to highly functionalized sultam and sultone derivatives in 75–95% yield under mild conditions. Density functional theory studies have been used to explain the regioselectivity in the synthesis of the coumarin- and quinolone-fused sultams and sultones.
Keywords: sultams; sultones; regioselectivity; density functional theory